Enhancing Critical Thinking Skills of Biology Students Through the Development of STEM-Based Invertebrate Zoology Teaching Materials - Kasmiruddin; Endang Widi Winarni; Abdul Rahman (Postgraduate, University of Mataram, 2025)
This study aimed to enhance biology students’ critical thinking skills through the development of STEM-based instructional materials for the Invertebrate Zoology course. Employing a design and development research approach using the ADDIE model, the study involved needs analysis, module development, expert validation, practicality testing, and effectiveness evaluation. The materials integrated STEM elements including ecological measurement tools, technological media, specimen preparation, and data analysis. Validation by experts yielded a 98% score, indicating high validity. Practicality tests showed increasing student satisfaction across individual (83.47%), small group (85.66%), and full-class trials (94.30%). The effectiveness was assessed using a one-group pretest-posttest design. The Wilcoxon Signed-Rank test revealed a statistically significant improvement in students’ critical thinking skills (p = 0.000). Posttest results showed that 66.67% of students reached the “very good” category and 33.33% were in the “good” category, with a mean score of 84%. Among Ennis' critical thinking indicators, “defining terms” had the highest score (95.24%), while “generalizing from evidence” scored the lowest (72.38%). These findings indicate that STEM-integrated teaching materials can effectively foster students’ higher-order thinking in biology education.